2018
DOI: 10.1002/apj.2263
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of shale rock wettability and the methods to determine it

Abstract: Because of ultra-low permeability of shale rocks, capillary pressure is very high. Wettability not only determines the value of capillary pressure, but, more importantly, it also determines whether the capillary pressure is a driving force or a resistance to fluid flow. This paper is to address the wettability characteristics of shale rocks. First, the common methods to determine wettability are reviewed and discussed for their feasibility for shale rocks. It is found that the real reservoir wettability must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…According to the published data, the contact angle for shale rock may vary from 11 to 103 • (Sheng, 2018;Siddiqui et al, 2018). For example, Lower Silurian Longmaxi shale samples are characterized by an 11-39 • contact angle (strongly water-wet).…”
Section: Discussionmentioning
confidence: 99%
“…According to the published data, the contact angle for shale rock may vary from 11 to 103 • (Sheng, 2018;Siddiqui et al, 2018). For example, Lower Silurian Longmaxi shale samples are characterized by an 11-39 • contact angle (strongly water-wet).…”
Section: Discussionmentioning
confidence: 99%
“…It was highlighted earlier that previous investigations of shale hydration under confinement were performed under dynamic imbibition conditions where some injection pressure was used to hydrate the core (Sheng & Sheng, ; Zhang & Sheng, , ). However, in this study, to represent truly SI conditions, the core holder cap was left slightly untightened leaving a small space between cap and the sample surface, Figure .…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Siddiqui et al (2018) recently opined in their comprehensive review that CA-based wettability estimated in an oil-water system is consistent rather than in an air-water system. Later, Sheng (2018) concluded that even SI should be performed in an oil-water system. Despite this, the reasons for inconsistency between air-fluid CAs and air-fluid SI have not been identified yet-which will be explored in this study.…”
Section: Introductionmentioning
confidence: 99%
“…e higher the maturity of organic matter, the stronger the lipophilicity [30]. e simultaneous appearance of inorganic water-wet macropores and organic oil-wet small pores makes shale have double wettability, which is also where the wettability of shale oil reservoirs is different from that of conventional reservoirs [31].…”
Section: Introductionmentioning
confidence: 99%